Musical door bell / Mohd Azuan Abdul Aziz and Roslan Bakar - Abdul Aziz, Mohd Azuan; Bakar, Roslan (2001)
The musical door-bell generates 16 different notes in three seconds and repeats the cycle for about ten seconds when the ‘press switch’ is pushed momentarily. This circuit consists of clock oscillator using the popular timer 1C 555, 4 bit-bmary counter 7493 and digital-to-analogue converter using four resistors. Basic audio oscillator is using a timer and an electronic delay switch. The clock oscillator is construct around IC 555. This clock output is fed to the ‘clock in’ of the 4 bit-binary counters or divide-by-sixteen counter. Whenever the pulse is applied at clock input, it produces a 4 bit-binary equivalent code at its four output lines. A small 8-ohm speaker connected across the output of this audio oscillator produces the musical tones.